Museo Julio César Cubillos : patrimonio arqueológico de la Universidad del Valle - Rodríguez, Carlos Armando, 1952- (Colección Artes y humanidades (Universidad del Valle), 2015)
Through the use of the visual resource, the particularities that characterize the work of artists from 11 Pre-Hispanic cultures of Colombia are studied and analyzed.